Behavior of Camel Browsing Maintained on Vegetation at Desert, Irrigated and Costal Zones of Sindh-Pakistan: Surveillance and Preference of Camel Browse Vegetation - Khaskheli, Asad Ali; Khaskheli, Muhammad Ibrahim; Khaskheli, Gul Bahar; Khaskheli, Allah Jurio; Khaskheli, Arshad Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Present research focused three major districts viz Mithi, Tando Allahyar and Thatta from Desert, Irrigated and Coastal zones of Sindh Province of Pakistan during the year 2018. Study was subjected to screen and assess the preference pattern of the camel browse vegetations surrounding the study area. Results of present study indicated a total of 16 natural vegetations at Mithi, 16 at Tando Allahyar and 19 at Thatta which were found to be available forbrowsing by the camels. Further, results reveled Senegalia senegal the most preferred vegetation followed by Cordia sinensis (Linn.), Salvadora oleiodes, and Ziziphus nummularia while, Prosopis juliflora appeared less preferred (p<0.05) followed by Calligonum polygonoides, Orthanthera viminea and Prosopis cineraria at district Mithi. At Tando Allahyar district camel preferred (p<0.05) more to browse the Salvadora oleiodes followed by Suaeda fruticosa, Haloxylon salicornicum and Acacia nilotica and less the Prosopis juliflora, while Tamarix passerinoides followed by Mudhari Tribulus terrestris and Melilotus parviflora were moderately preferred by camels. Further results showed that the Cordia sinensis (Linn.) (p<0.05) was browsed more by camels at Thatta followed by Salvadora oleiodes, Suaeda fruticosa, Haloxylon salicornicum and Prosopis juliflora preferred less. However, Alhagi maurorum, R.mucronata and Timar Avicenia officinalis are preferred by camels at intermediate level. Study concludes that the coastal zone possess significantly ((p<0.05) higher number of natural vagetations for camel browsing comparatively desert and irrigated zones. Senegalia Senegal, Salvadora oleiodes, Cordia sinensis (Linn.) are the most favorite vegetations for camel at all zones but the Prosopis juliflora is less preferred.